COGNITIVE OVERLOAD MANAGEMENT: EMPOWERING SIMULATION BASED MEDICAL EDUCATION THROUGH MINDFUL REALITY CHECKS. (13th May 2015) - Khan, Erum
Abstract : Aims: To guide the design of simulation based instructions consistent with the nature of human cognitive architecture. Background: Cognitive load is the effort required for information handling in the working memory. There is a wealth of research on Human cognition and Instructional science that suggests that effective and efficient instructional strategies should avoid overloading the limited capacity of the working memory; a theory called "Cognitive Load Theory". The foundational fact of this theory which is critical to any instructional strategy is that beyond a certain limit the cognitive overload starts impairing student learning. Description of Innovation Topic: At Center for Advanced Simulation in Healthcare, Gulf Medical University; simulation based instructions are designed keeping the human cognition in mind. Appropriately planning, integrating and aligning the clinical content and skills with the level of the learner takes care of the content load (Intrinsic load) while on the other hand constructively designing the simulation session with appropriate use of the simulation fidelity, pre-scenario briefing, simulator and learning environment orientation and debriefing facilitation skills matching the expectation, motivation level and interest of the learners ensures a mindful check on the extraneous and germane load that arises when learners interact with the instructional material. Conclusions: Simulation Educators should aim to understand the causes of cognitive overload and stress and have strategies to minimize their impact. Keeping a mindful watch out and frequent reality checks on the intrinsic and extrinsic load of the simulation exercises is highly recommended. We recommend the use of pre-session materials and advanced organizers, a comprehensive pre-briefing and debriefing, small peer group frequent simulation exercises with increasing level of challenges.